Approach to four creations dealing with Manuel Rodríguez from the point of view of silent movies times journalism critique and pre cinema era journalism critique . - Jara, Eliana; Maturana, Carmen Luz (Universidad de Chile. Instituto de la Comunicación e Imagen, 2012)
An approach to three silent movies is dealt together (1925; 1920; 1910) with a visual show of the pre-cinema era (1824), all of this is referred to Manuel Rodriguez. The analysis is centered in understanding through a delimited linguistic study of how they are referred to in printed texts of those days. Journalism records allow a rapprochement to the birth of cinema critique in Chile from a theme axis interested in its emergence and evolution. The main conclusions show a progressive delimitation on the part of the critique of the working areas involved in the creation, as much as a gradual differentiation between the theatrical and the cinematic acting. Furthermore, any negative consideration is diminished apart and is giving human actions to the visual material as a way of being able to define it in a more concrete manner.